Does internet connectivity affect export performance? Evidence from the transition economies - George R. G. Clarke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Over the past few years, many commentators have suggested that the Internet is one of the forces driving globalization. This paper tries to assess one aspect of these claims, looking at whether Internet access appears to affect the export performance of enterprises in low- and middle-income economies in Eastern Europe and Central Asia. The papers finds that even after controlling for self-selectivity bias and for factors that might affect both exports and Internet connectivity, enterprises with Internet access appear to export more than similar enterprises without access. Further, Internet access appears to affect industrial and service enterprises to similar degrees. – exports ; information technology ; FDI
Keywords: F15; O14; O30; 330; Internationales Marketing; Internet; Welt